HUBUNGAN MOTIVASI DIRI DENGAN KEPATUHAN DIET PADA PENDERITA DIABETES MELITUS TIPE 2 - Dwi Putri Lumban Toruan; Darwin Karim; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Diabetes mellitus (DM) is a metabolism desease that characterized by increasing high blood glucose because insulin secretion impairtment and it caused acute and chronic complication. This research aimed to determine the correlation between self-motivation and diet adherence in patients with diabetes mellitus type 2. This research method used descriptive correlation with cross sectional approach. This research was conducted in Puskesmas Harapan Raya Pekanbaru against 40 respondents taken by using purposive sampling technique. Instrument used was questionnaires that was tested it is validity and reliability and 24 Hour recall Table. Analyze test used was univariate analysis with the results highest self-motivation who adhere to the diet as many as 21 respondents (52,5%) and lowest dietary compliance as many as 24 respondents (60%). Bivariate analysis used was Chi-Square test with the result showed that highest self-motivation who comply to diet as many as 13 respondents (61,9%). After the bivariate analysis obtained p value (0.003) < α (0.05). The conclusion of this research is that there is correlation between self-motivation and dietary compliance of patients with type 2 diabetes in Puskesmas Harapan Raya Pekanbaru. Based on the results of the research, it is expected Puskesmas can provide information and identify self-motivation issues and diet adherence associated with efforts to improve health care in diabetic patients, therefore it can improve optimal treatment.  Keywords: Diabetes mellitus, dietary compliance, self-motivation